Correlation between Adsorption and Porosity Properties of Alumina Samples as Obtained from Classical Adsorption and Thermal Analysis Methods - M. Płanda; P. Staszczuk; J. Pękalska (Adsorption Science & Technology)
The thermodesorption of benzene and water from alumina samples saturated in vacuum desiccators was studied under quasi-equilibrium conditions. The Q-TG and Q-DTG curves obtained showed multi-step weight losses associated with the evaporation of liquid from pores and physisorbed liquid films from active centres of different energy. The adsorption/desorption isotherms of nitrogen on porous alumina samples were measured using sorptiomatic methods allowing the calculation of the corresponding pore size distribution functions. The water vapour sorption isotherms were measured gravimetrically employing an apparatus fitted with a McBain microbalance. A correlation between the porosity parameters and the volume of desorbed liquid is presented illustrating the good agreement obtained.